Three-dimensional linkage analysis with digital PCR for genome integrity and identity of recombinant adeno-associated virus - Tam Duong; Michele Firmo; Chien-Ting Li; Bingnan Gu; Peng Wang (Scientific Reports)
Abstract Recombinant adeno-associated virus (rAAV) has emerged as the vector of choice for in vivo gene delivery, with numerous clinical trials underway for the treatment of various human diseases. Utilizing rAAV in gene therapy requires a highly precise quantification method to determine the viral genome titer and further establish the optimal therapeutic dosage for a rAAV product. The conventional single-channel droplet digital PCR (1D ddPCR) method offers only partial information regarding the viral vector genome titer, lacking insights into its integrity. In our pursuit of further advancing rAAV analysis, we have developed a novel 3D ddPCR assay with advanced 3D linkage analysis. We have designed the three amplicon sites targeting both ends of the viral genome, as well as the center of key therapeutic gene of interest (GOI). This study aims to offer a more comprehensive and insightful assessment of rAAV products which includes not only quantity of viral genome titer but also the quality, distinguishing between partial ones and intact full-length viral genomes with the right GOI. Importantly, due to the random partitioning property of a digital PCR system, the 3D linkage analysis of rAAV viral genome requires a proper mathematical model to identify the true linked DNA molecules (full-length/intact DNA) from the population of false/unlinked DNA molecules (fragmented/partial DNA). We therefore have developed an AAV 3D linkage analysis workflow to characterize genomic integrity and intact titer for rAAV gene therapy products. In this study, we focus on evaluating our 3D linkage mathematical model by performing DNA mixing experiments and a case study using multiple rAAV samples. Particularly, we rigorously tested our algorithms by conducting experiments involving the mixing of seven DNA fragments to represent various AAV viral genome populations, including 3 single partials, 3 double partials, and 1 full-length genomes. Across all 37 tested scenarios, we validated the accuracy of our workflow’s output for the percentages of 3D linkage by comparing to the known percentages of input DNA. Consequently, our comprehensive AAV analytical package not only offers insights into viral genome titer but also provides valuable information on its integrity and identity. This cost-effective approach, akin to the setup of traditional 1D or 2D dPCR, holds the potential to advance the application of rAAV in cell and gene therapy for the treatment of human diseases.